Enhancing Biology Molecular Laboratory Practice for Senior High School of Biology Teachers from Samarinda and Tenggarong City - Retno Aryani; Rudy Agung Nugroho; Hetty Manurung; Rudianta Rudianta; Auliana Auliana; Widha Prahastika (Pelita Eksakta, 2018)
Teacher as one of the important key factors in education must enhance the quality of their knowledge both theoretical, skills, and expertise. For this reason, the community service program held by Department of Biology, FMIPA, Mulawarman University, Samarinda aimed to improve the practical skills of high school teachers. This program was attended by 16 teachers from various high schools from the Samarinda region and Tenggarong. The community service program consisted of 25% theory and 75% practice in one day. The theory about DNA isolation, polymerase chain reaction, and electrophoresis was done in the classroom. Meanwhile, in laboratory, the use of molecular biology equipment, electrophoresis, interpretation results of electrophoretic DNA bands, and NCBI was done by the teachers which is assisted by the laboratory assistant. In the end of the program, the skill of laboratory practice of teachers was improve, indicating by the increasing percentage of understanding about biology molecular skills.